Nonmosaic Isodicentric Y Chromosome: A Rare Cause of Azoospermia— From Genetics to Clinical Practice. (26th July 2020) - Van Cauwenberghe, Jolijn; Beckers, Sigri; Coremans, Peter
Abstract : Azoospermia is diagnosed when no spermatozoa can be detected after centrifugation of seminal fluid on at least two separate occasions. A number of genetic disorders can be related to nonobstructive azoospermia, and in up to 15% of azoospermic males, a genetic disorder is diagnosed. A 36-year-old male with nonobstructive azoospermia was referred to our department of diabetes and endocrinology due to an aberrant testicular biopsy. The biopsy showed a disrupted spermatogenesis with a maturation arrest at the spermatocyte level in most tubuli seminiferi while others showed a Sertoli cell-only syndrome. Screening for Y chromosome microdeletions on peripheral blood using molecular analysis detected a terminal deletion of AZFbc. The result of karyotyping and fluorescence in situ hybridization (FISH) described an isodicentric Y chromosome with karyotype 46, X, idic(Y)(q11.22). Based on this case and the current available literature, we conclude that performing a testicular biopsy in patients with a nonmosaic idic(Y)(q) is not meaningful and that the prognosis on infertility is poor. Biological fatherhood is extremely unlikely in these patients, and proper counselling should be provided.